The dynamics of exchange rates in emerging countries: a Post-Keynesian perspective for the cases of Brazil and Mexico between 2000 and 2017 - Tellez Marins, Nathalie; Magalhães Prates, Daniela (Brazilian Keynesian Review, 2020)
In the post-Keynesian view, the exchange rate is considered a financial asset class subject to investment decisions of investors in a hierarchical and asymmetric international monetary and financial system. Based on this theoretical reference, this paper conducts a comparative case study of the exchange rates of Brazil and Mexico during the 2000s. The goal is to highlight the influence of institutional on the exchange rate dynamics. The study covers six phases of the international liquidity cycle, using the Exponentially Weighted Moving Average method and the Pearson coefficient. The results show that, although the exchange rates studied have a very similar co-movement, there are important differences regarding their volatility and the impact of the theoretical determinants.